Absolutely summing polynomials - Ribeiro, J.; Santos, F. (Methods of Functional Analysis and Topology, 2021)
In this paper, we introduce an abstract approach to the notion of absolutely summing polynomials, and we explore several of its properties, among them that this class is a Banach ideal of homogeneous polynomials. As a consequence of the abstract approach introduced in this paper, we show that in addition to obtaining several previous results in different contexts as particular cases, it is possible to easily create new classes of homogeneous polynomials that are absolutely summing. Розвинуто абстрактний підхід до поняття абсолютно підсумовуючих поліномів. Досліджуються їхні властивості, зокрема, показано, що цей клас є банаховим ідеалом однорідних поліномів. Наслідком абстактного підходу є не тільки результати, отримані раніше для спеціальних випадків, але й можливість побудови нових класів абсолютно підсумовуючих поліномів.